ChemInform Abstract: Molecular Iodine Catalyzed Transfer Hydrogenation: Reduction of Aldimines, Ketimines, and α‐Imino Esters. Issue 44 (14th October 2013) - Bachu, Prabhakar; Zhu, Chen; Akiyama, Takahiko
Abstract A facile protocol using molecular iodine as the catalyst and Hantzsch ester as hydrogen source allows the conversion of aldimines, ketimines and α‐imino esters into the corresponding amines under mild reaction conditions.